Postfeeding radial dispersal in larvae of Chrysomya albiceps (Diptera : Calliphoridae): implications for forensic entomology - Gomes, L.; Von Zuben, C. J. (Elsevier B.V., 2005)
Blowflies utilize discrete and ephemeral breeding sites for larval nutrition. After the exhaustion of food, larvae begin dispersing in search of sites to pupate or additional food sources, a process referred as postfeeding larval dispersal. Some of the most important aspects of this process were investigated in the blowfly Chrysomya albiceps, employing a circular arena to allow radial dispersion of larvae from the center. The results showed a positive correlation between burial depth and distance, and a negative correlation between distance and pupal weight. These results can be used in forensic entomology for the postmortem interval estimation of human corpses in medico-criminal investigations. (c) 2004 Elsevier B.V.. All rights reserved.
Keywords: blowfly; forensic entomology; larval dispersal